Penyalahgunaan Akun pada Handphone Iphone Perspektif Ibnu Taimiyah (Studi pada Akun Jual Beli Online di Kota Medan) - Munthe, Muhammad Royhan; Harahap, Abd. Rahman (Fakultas Syariah INSURI Ponorogo, 2023)
Collaboration with iPhone users is cooperation in the form of services in providing a visual display by providing photo and video services via iPhone mobile phones. To do this, the owner of an online buying and selling account must provide the password from his buying and selling account to the iPhone service and video owner. The purpose and focus of this research is to find out the law of cooperation on the iPhone in the Islamic perspective of Ibnu Taimiyah in the city of Medan. The methods used by the author are Library Research and Field Research with a normative-empirical approach. The results of this study are based on the perspective of Ibnu Taimiyah which is related to all kinds of business, namely to uphold justice in doing business. Therefore, cooperation in photo and video services for iPhones is very dangerous for personal data and in this collaboration there is no la dharar principle, namely the principle of not hurting each other.